2021
DOI: 10.1371/journal.pone.0254759
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two closely related citrus cultivars using UPLC-ESI-MS/MS-based widely targeted metabolomics

Abstract: Citrus cultivars are widely spread worldwide, and some of them only differ by specific mutations along the genome. It is difficult to distinguish them by traditional morphological identification. To accurately identify such similar cultivars, the subtle differences between them must be detected. In this study, UPLC-ESI-MS/MS-based widely targeted metabolomics analysis was conducted to study the chemical differences between two closely related citrus cultivars, Citrus reticulata ‘DHP’ and C. reticulata ‘BZH’. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…However, no specific data is reported regarding the content of RGL bioactive compounds. Similar studies have identified bioactive compounds from Mandarin Oranges belonging to the same species as RGL (Wang et al 2021). However, the results of the study showed that the typical compounds in each type of mandarin orange could be different even though they came from the same species (Wang et al 2021).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, no specific data is reported regarding the content of RGL bioactive compounds. Similar studies have identified bioactive compounds from Mandarin Oranges belonging to the same species as RGL (Wang et al 2021). However, the results of the study showed that the typical compounds in each type of mandarin orange could be different even though they came from the same species (Wang et al 2021).…”
Section: Introductionsupporting
confidence: 53%
“…Similar studies have identified bioactive compounds from Mandarin Oranges belonging to the same species as RGL (Wang et al 2021). However, the results of the study showed that the typical compounds in each type of mandarin orange could be different even though they came from the same species (Wang et al 2021). In addition, most of the reported data regarding the compounds present in the RGL citrus species are the result of HPLC, so it has not been possible to analyze large amounts of bioactive compounds simultaneously (Abeysinghe et al 2007;Mei et al 2021).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Guo et al detected 134 metabolites grouped into 11 classes in blueberry [ 32 ]. Chen et al identified 407 metabolites in strawberry [ 33 ], while 352 metabolites were detected and identified in citrus [ 34 ]. Ma et al identified 464 metabolites in berry skin [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we adjusted the extraction, characterization, and quantification of metabolites based on Wang et al [35], as briefly stated below.…”
Section: Fresh Amla Fruit Extraction Characterization and Quantificat...mentioning
confidence: 99%